Homonymy in Online Media CNN Arabic and Al-Wathon in Crime News on the Internet - Intan Handita Kuswoyo; Aimmatul Mufarrihah; Alawiyah Zuhri (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
n semantic studies, semantic relations can express similarity of meaning, different meaning, scope of meaning, more meaning and multiple meaning. Linguistic factors are natural phenomena of language. And diachronically, language changes are possible, including changes in the meaning of words. Thus, it can cause misunderstandings in context. The discussions that will be carried out in this research include (1) explaining the meaning of homonymy, (2) explaining the various types of homonymy and including examples and explanations of the examples listed. With the aim of readers being able to understand what homonymy is in Arabic and examples. In order to achieve this goal, a qualitative research method was used using CNN Arabic and Al-Wathan data sources by quoting some sentences from the media. Next, data was collected using the document study method and analyzed. In this case, the news taken is about one of internet crime (cyber crime) which was published on the online media CNN Arabic and on the online media Al-Wathan. The results of this research are that there was no homonymy between morphemes, while homonymy between words, homonymy between phrases and between sentences were found in the news that we took from CNN Arabic and Al-Wathon media.